Hybrid manufacturing and performance evaluation of β Ti-alloy stents - Peter Ibrahim; Rebecca Garrard; Pavel Penchev; Kenny Man; Sophie C. Cox; Stefan Dimov; Moataz M. Attallah (Materials & Design)
Biomedical β Ti-alloys possess an interesting combination of mechanical properties, including an elastic modulus lower than 60 GPa. In this study, a hybrid manufacturing route for Ti-34Nb-13Ta-5Zr-0.3O (TNTZO) alloy stents was developed and assessed. The route involves using Laser Powder Bed Fusion (L-PBF) to manufacture thin-walled tubes, which are then laser micro-machined to directly produce customised stents, cutting short the laborious process and overcome the design limitations for stents manufacturing. Different post processing techniques were used to improve the surface finish and cell attachment properties of the tubes. Finite Element (FE) modelling was used to simulate stent crimping and deployment. The study identified the key parameters that control the performance of the final product, including the optimum laser scanning strategies during L-PBF to achieve smooth thin-walled tubes, and the use of electropolishing to improve the surface finish and cell attachment. FE simulations showed that TNTZO can achieve crimping ranges up to 74% following the optimisation of the strut diameter, which brings us one step closer to a Ni-free alternative to nitinol in manufacturing stents that require significant deformation.